Comparing rolling resistance of two treadmills and its influence on exercise testing in wheelchair athletics - Arnet, Ursina; Ammann, Fabian; Perret, Claudio (Frontiers in Psychology, 2023)
Standardized laboratory exercise testing is common in sport settings and rehabilitation. The advantages of laboratory-based compared to field testing include the use of calibrated equipment and the possibility of keeping environmental conditions within narrow limits, making test results highly comparable and reproducible. However, when using different equipment (e.g. treadmills), the results might deviate and impair comparability. The aim of this study was to compare the biomechanical properties (rolling resistance, speed, inclination) of two treadmills regularly used for exercise testing in elite wheelchair athletes. During the experiment, speed and inclination of two treadmills (same model and producer, different manufacturing year and belt material) were verified. Standardized drag tests were performed to assess rolling resistance. Power output conducted by the athlete during later exercise tests was calculated based on the results. Speed and inclination deviated only slightly from the values indicated by the producer. Rolling resistance caused by different belt material was mainly accountable for the differences in power output between the treadmills. In general, athletes had to deliver 10% more power output on one of the treadmills compared to the other. Concluding from these results: if different treadmills are used for testing, a proper validation is recommended to avoid misleading interpretations of test results.